2013
DOI: 10.1136/jnnp-2012-304157
|View full text |Cite
|
Sign up to set email alerts
|

Impaired social cognition in multiple sclerosis

Abstract: These results suggest impaired social cognition in MS. Importantly, ToM impairments in this group may not simply be a consequence of the well known neuropsychological deficits. Difficulties with correctly identifying emotions, thoughts and intentions in social situations may result in interpersonal problems and could contribute to the psychosocial burden of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 48 publications
7
79
1
6
Order By: Relevance
“…McGuire et al, 2009 Reniers et al, 2011). Third, the current study did not directly assess ToM deficits in MS population, but we do note the substantial literature demonstrating these deficits in MS patients (Banati et al, 2010;Charvet et al, 2014;Henry et al, 2009Henry et al, , 2011Kraemer et al, 2013;Ouellet et al, 2010;Pöttgen et al, 2013;Roca et al, 2014). Fourth, this was an exploratory study that found EOT to play an important role in moral cognition, and thus future studies need to further explore the exact mechanism by which this dimension of alexithymia interacts with incidental affect and how this interaction has downstream consequences for moral judgments.…”
Section: Methodologicalmentioning
confidence: 98%
See 1 more Smart Citation
“…McGuire et al, 2009 Reniers et al, 2011). Third, the current study did not directly assess ToM deficits in MS population, but we do note the substantial literature demonstrating these deficits in MS patients (Banati et al, 2010;Charvet et al, 2014;Henry et al, 2009Henry et al, , 2011Kraemer et al, 2013;Ouellet et al, 2010;Pöttgen et al, 2013;Roca et al, 2014). Fourth, this was an exploratory study that found EOT to play an important role in moral cognition, and thus future studies need to further explore the exact mechanism by which this dimension of alexithymia interacts with incidental affect and how this interaction has downstream consequences for moral judgments.…”
Section: Methodologicalmentioning
confidence: 98%
“…In particular, MS patients perform poorly in extracting information about intentionality, representing first-and second-order false beliefs, and detecting social faux pas in verbal/nonverbal ToM assessment tasks (Banati et al, 2010;Charvet et al, 2014;Henry et al, 2011;Pöttgen et al, 2013;Roca et al, 2014). These deficits remain even after controlling for the co-occurring neuropsychological impairments, such as executive function deficits (Charvet et al, 2014;Pöttgen et al, 2013). Importantly, ToM deficits appear from the very early stage of the disease in young adults (Kraemer et al, 2013) and are found even in pediatric-onset MS patients (Charvet et al, 2014).…”
Section: Ms and Deficits In Social Cognitionmentioning
confidence: 99%
“…In the same year, Ouellet arrived at the conclusion that patients with MS suffering from cognitive deficits tend not to recognize the mental state of others unlike MS patients with preserved cognition (15 cognitively intact and 26 cognitively impaired patients) [49], while Henry (64 patients with relapsing-remitting MS (RRMS), 30 controls) [78] and Pöttgen (45 patients with MS, 45 healthy controls) [21] found that ToM deficits in MS appear independently of the well-known cognitive deficits. Emotion recognition impairments were more pronounced in patients with MS than impairments in thought and intention recognition [21,79].…”
Section: Social Cognition Impairments In Patients With Multiple Sclermentioning
confidence: 99%
“…ToM is viewed as a specific capacity of the mind to understand ourselves and others in terms of mental states. It is based on "reading the thoughts and emotions" of others through analyzing their facial expressions and other behavioral signs [21,22]. ToM provides the opportunity for establishing a connection between internal conditions manifested through expressions, gestures, signals and internal states of mind.…”
Section: What Is Social Cognition?mentioning
confidence: 99%
See 1 more Smart Citation